Association between Low-Density Lipoproteins (LDL) and Cardiovascular Disease in Patients with Chronic Kidney Disease at Kutchum Hospital, Yasothon Province - Chaiyarat, Pimploy; Khemphet, Nuntiya; Maneenin, Naowarat; Maneenil, Chanwit; Jirapornkul, Chananya (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2025)
Cardiovascular disease (CVD) is a major complication that can occur in patients with chronic kidney disease (CKD), from early to end-stage, with a prevalence 2–4 times higher than in the general population. The objectives of this study were to determine the incidence of cardiovascular disease and to examine the association between low-density lipoprotein cholesterol (LDL-C) levels and the occurrence of cardiovascular disease in CKD patients at Kutchum Hospital, Yasothon Province. This was a retrospective analytical study. Data were obtained from the medical records of 257 CKD patients who received treatment at Kutchum Hospital, Kutchum District, Yasothon Province, between October 1, 2012, and September 30, 2023. All patients were followed from the time of chronic kidney disease diagnosis until cardiovascular disease occurrence. The association was analyzed using generalized linear models (GLMs). The results showed that the incidence of cardiovascular disease among chronic kidney disease patients was 31.5%. Patients with LDL-C levels ≥100 mg/dL had a 2.05-fold increased risk of developing cardiovascular disease compared to those with LDL-C levels <100 mg/dL (adjusted RR = 2.05, 95%CI: 1.33–3.18, p = 0.001). This study found that LDL-C levels were significantly associated with the occurrence of cardiovascular disease. The incidence of cardiovascular disease among chronic kidney disease patients with LDL-C levels ≥100 mg/dL showed an increasing trend. Therefore, screening and control of LDL-C levels should be implemented to maintain levels below 100 mg/dL in patients with chronic kidney disease, alongside strengthened individualized care. In addition, educational interventions for cardiovascular disease prevention should be enhanced, particularly for overweight individuals and those with a CKD duration of more than five years. These interventions intend to enhance awareness and promote self-care practices for cardiovascular disease prevention.